2019
DOI: 10.9734/ajaar/2019/v10i230026
|View full text |Cite
|
Sign up to set email alerts
|

Farmers Attitude towards Organic Farming: A Case Study in Chapainawabganj District

Abstract: The main purpose of the study was to evaluate farmers socio-economic status, attitude and relationship among them towards organic farming. The study was conducted in five upazilas of Chapainawabganj district in Bangladesh. A simple random sampling technique was used to select 40 respondents. Attitude of respondents toward organic farming was measured with twenty statements using five point likert type scales. To explore the relationship between the concerned variables correlation coefficient (r) was computed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 6 publications
(6 reference statements)
1
6
0
Order By: Relevance
“…There is a positive correlation between converting to organic farming and farm size. A study in India indicated that large farm holding can result in a shift to organic farming [57]. More so, the fragmentation of land in the country particularly in the rural settlement has limited the expansion of large-scale farming systems and which could inhibit organic farming [58].…”
Section: Discussionmentioning
confidence: 99%
“…There is a positive correlation between converting to organic farming and farm size. A study in India indicated that large farm holding can result in a shift to organic farming [57]. More so, the fragmentation of land in the country particularly in the rural settlement has limited the expansion of large-scale farming systems and which could inhibit organic farming [58].…”
Section: Discussionmentioning
confidence: 99%
“…So, to persuade farmers to employ organic farming as one of the sustainable agricultural systems, it is important to recognize the AEW's attitude toward organic forming and the effect of its factors on extending and developing organic agricultural system among the farmers. Various studies have found the following effective variables: experience, education level, information resources and research projects (Wheeler, 2005(Wheeler, , 2008(Wheeler, , 2008; participation in courses and workshops as information resources (Pourjavid and Ghanian, 2019;Hasan et al, 2017;Oluwasusi, 2014); work experience, education level and use of mass media Hooshmandan Moghaddam Fard, 2017, 2016;Ghosh et al, 2019); educational and information factors (Jesarati et al, 2018); age and education level (Herath and Wijekoon, 2013;Patidar and Attitude toward organic agribusiness Patidar, 2015;Pushpa Malkanthi, 2020); and reading research articles and related Internet websites journals and the use of the Internet (Khoshmaram et al, 2015). In this regard, the results of literature review show that age, educational levels, work experience, number of information sources, use of social networks, book reading, participation in seminars and reading research articles affect the attitude toward organic agribusiness.…”
Section: Attitude Toward Organic Agribusinessmentioning
confidence: 99%
“…Farmers' attitude towards adoption is strongly correlated with farmers' perceived behavioural control (how they perceive the level of difficulty in adopting) and their self-belief in the capacity to adopt and then maintain the practice [43]. For example, farmers' attitudes towards agroforestry were strongly related to the level of access to information and extension support in Bangladesh [44].…”
Section: Farmer Capacity To Adoptmentioning
confidence: 99%